Awareness of the Implications of the Impending Product Patent Regime on the Indian Pharmaceutical Market: A Questionnaire Study - Wadhwa, Navneet (Indian Journal of Marketing, 2005)
India is signatory to Trade Related Intellectual Property Rights (TRIPs) agreement under the World Trade Organization (WTO), which would enter into force on 1 January 1995. Hence, the year 2005 is bound to be a watershed year for the Indian pharmaceutical industry as it steps into the new product patent regime. This agreement requires the member nations of WTO, including India to live up to the defined standards of intellectual property protection. The emergence of TRIPs in the WTO is the catalyst that led to changes in India’s policy on patents. India’s patent policy, which earlier emphasised public interest over monopoly rights, is in the process of shifting this balance towards greater protection of intellectual property rights. (The Economist, April 2001). Reforms are being undertaken to conform to stipulations in the TRIPs agreement. There is a domestic shift in the approach to patents, which is also leading to policy revisions, and eventually this would confer greater patent protection.